Pulsed electric fields as a green technology for the extraction of bioactive compounds from thinned peach by-products. (February 2018) - Redondo, Diego; Venturini, María E.; Luengo, Elisa; Raso, Javier; Arias, Esther
Abstract: Thinned fruits are agricultural by-products which nowadays have few economic or environmental benefits. However, previous studies have revealed that these immature fruits have a large amount of antioxidant compounds. The aim of this study was to evaluate whether pulsed electric fields (PEF) might be a suitable green technology for enhancing the extraction of phenols, flavonoids and antioxidant compounds from fresh thinned peaches, thus reducing the use of methanol. Moreover, response surface methodology has been used to determine the optimal PEF treatment conditions, observing that the solvent is the main factor. The highest amounts of bioactive compounds were extracted using 80% methanol and no PEF. Methanol combined with PEF produced a negative effect on the extraction yield. However, the use of water as a solvent increased the amount of total bioactive compounds and individual phenols (chlorogenic acid, coumaric acid and neochlorogenic acid). Thus, PEF-assisted extraction of bioactive compounds from thinned peach fruits using water as a solvent is an alternative to conventional extraction methods which require dried products, large amounts of organic solvents and long extraction times. Highlights: Solvent is the main factor for extraction of bioactive compounds from thinned fruits Application of PEF is very effective when water is used as solvent PEF extraction of phenol compounds stands as a green alternative to conventional ones